The Influence of Parental Attention on The Learning Motivation of Junior High School Students in Riau - Safitri, Yupita; Risnawati, Risnawati; Za’ba, Nasir (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Motivation is the main element in determining learning success. However, the reality in the field shows that there are still students whose motivation to learn is low. The role of parents is very important in students' learning motivation, such as parents' attention to their children. In fact, students' learning motivation is low due to lack of attention from their parents. The aim of this research is to determine the influence of parental attention on students' learning motivation in Islamic Religious Education subjects. The method used in this research is a descriptive quantitative method. Data was collected through a questionnaire that focused on the variables of parental attention and student learning motivation, with a measurement scale using a Likert scale. The results of the research stated that there was an influence of parental attention on students' learning motivation which was obtained based on the significance value from the coefficients table, obtaining a significance value of 0.000 0.05, so it could be concluded that variable X (parental attention) had an influence on the participation variable Y (learning motivation).